The vascular epigenome in patients with obesity and type 2 diabetes: opportunities for personalized therapies. (10th June 2020) - Costantino, Sarah; Mohammed, Shafeeq A; Ambrosini, Samuele; Paneni, Francesco
Abstract : Our genetic background provides limited information on individual risk of developing vascular complications overtime. New biological layers, namely epigenetic modifications, are now emerging as potent regulators of gene expression thus leading to altered transcriptional programs and vascular disease phenotypes. Such epigenetic modifications, defined as changes to the genome that do not involve changes in DNA sequence, are generally induced by environmental factors and poor lifestyle habits. Of note, adverse epigenetic signals acquired during life can be transmitted to the offspring thus leading to premature alterations of the epigenetic and transcriptional landscape eventually leading to early endothelial dysfunction and vascular senescence. Modifications of the epigenome play a pivotal role in the pathophysiology of cardiometabolic disturbances such as obesity and type 2 diabetes. In these patients, changes of DNA methylation and chromatin structure contribute to alter pathways regulating insulin sensitivity, glucose homeostasis, adipogenesis and vascular function. In this perspective, unveiling the 'epigenetic landscape' in cardiometabolic patients may help to identify new players implicated in obesity and diabetes-related vascular dysfunction and may pave the way for personalized therapies in this setting. In the present review, we discuss current knowledge of the epigenetic routes implicated in vascular damage and cardiovascular disease in patients with metabolic alterations.